Lo compartido culturalmente como elemento indispensable para el estudio de las prácticas de recursos humanos en las organizaciones mexicanas: un enfoque conceptual. (The culturally shared as an indispensable element in the study of human resources practices in Mexican organizations: a conceptual approach) - Mendoza Gómez, Joel; Rositas Martínez, Juan (Facultad de Contaduría Pública y Administración U.A.N.L., 2011)
Abstract. In this conceptual article, a group of cultural elements are offered to study the possible influence of the culture on human resources practices and on elements related with these practices. Theoretical elements of culture, of work culture, of organizational culture, and of work groups’ shared mental model are reviewed.